Development Interactive videos as Learning Objects on Web Design Courses in the Education Technology at the State University of Jakarta - KUNTO IMBAR NURSETYO, S.Pd,M.Pd.; Drs. Erry Utomo, M.Ed, Ph.D.; Lutfan Kemal (Universitas Negeri Jakarta, 2020)
This study aims to develop interactive videos as Learning Objects on Web Design Courses in the Education Technology at the State University of Jakarta. The study material is using LMS plugins such as H5P and TablePress to create learning content, it also uses CMS plugins like Elementor to design the web on WordPress. This study uses the Dick & Carey development model, in this model the researcher only did 9 stages of developing Dick & Carey, only to the stage of Revise instructional. The subjects of this study were the 2017 University of Jakarta State University Education Technology students with a total of 17 students. The results of this study indicate that an expert review states this video is deserve and students for individual reviews with a average 3.86, and a small group review with a average 3.37, of the two reviews stated that students responded positively and this learning video is good and can be used as a Learning Object on Web Design Courses.